Analisis Isi Pesan Dakwah Arnita Rodelina Turnip Dalam Akun Youtube Rukun Indonesia - Vebby Adria Nengsih; Muhamad Fajri (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to analyze the content of the message of the dakwah Arnita Rodelina Turnip in Rukun Indonesia Youtube account. this study uses the theory of Da'wah message form of Da'wah message in the book Muhammad Qadaruddin Abdullah mecakupi problems of faith, Shari'ah, and morality. This research method uses qualitative research using a content analysis approach which involves the process of collecting data contained in Arnita's video on Rukun Indonesia's Youtube account. The subject of this study is a podcast sourced from Rukun Indonesia youtube account. data collection methods are observation and documentation. Content analysis was used to describe the content of Arnita Rodelina Turnip's dakwah message on Rukun Indonesia's Youtube account. The results of this study show the message of preaching arnita rodelina turnip video in rukun indonesia youtube account is the message of preaching the creed of belief in God, the message of preaching the Shari'ah about the obligatory prayers tahajud, and the message of preaching morals about tabayyun, Ta'aruf and tolerance.